Indonesia - Maulana Rifky Stansyah; Rahma Choirunnisa; Muhammad Tegar; Saint Seiya Ardhana Putri (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
The purpose of this research is to analyze and discuss the influence of consumer buying interest on the purchase of food and beverages through the Go Food application. This research is a causal research, that kind of research that is analyzed quantitatively. This research uses two data, namely primary data obtained from the results of questionnaire answers as many as 30 respondents and secondary data obtained from literature books, journals, scientific articles, and news articles related to the topic of discussion. The analysis technique used in this research is simple linear regression with the help of SPSS 23 software. The results show that there is a positive and significant influence on consumer buying interest in food and beverage purchasing decisions in the Go Food application.